Antioxidative Effects of Plant Polyphenols: From Protection of G Protein Signaling to Prevention of Age‐Related Pathologies - JEFREMOV, VIKTOR; ZILMER, MIHKEL; ZILMER, KERSTI; BOGDANOVIC, NENAD; KARELSON, ELLO (Annals of the New York Academy of Sciences, 2007)
Abstract : The antioxidant potency of three natural polyphenols, resveratrol, curcumin, and genistein, was compared by using the two human models: oxymodified with H 2 O 2 and homocysteine (Hcy) G proteins in the postmortem frontal cortex (FC) membranes of age‐matched control and Alzheimer's disease (AD) subjects; and Cu 2+ ‐induced oxidation of plasma low‐density lipoproteins (LDL). In Co, 3–10 μM polyphenols dose‐dependently depressed the G protein 25% stimulation induced by 10 μM H 2 O 2 or 500 μM Hcy. Resveratrol revealed significantly higher antioxidativity than curcumin or genistein. In AD, the antioxidativity of polyphenols showed no significant differences. Polyphenols (1 μM) significantly increased the LDL oxidation lag time (oxyresistance) as compared with control, the effect of resveratrol being most potent. Due to the dual antioxidant mechanism, the investigated polyphenols, particularly resveratrol, should have preferences for the preventive‐therapeutic use in age‐related oxidative stress‐based pathologies.